Co‐designing for success: Fostering psychological safety with learners to optimise learning, collaboration and performance. Issue 3 (20th January 2022) - Johnson, Christina E.; Leech, Michelle
Abstract : The authors discuss how co‐designing programs with students may foster psychological safety and encourage students to seek help and respond productively when faced with challenges.